2014
DOI: 10.1051/0004-6361/201424403
|View full text |Cite
|
Sign up to set email alerts
|

Forbidden oxygen lines at various nucleocentric distances in comets

Abstract: Aims. We study the formation of the [OI] lines -that is, 5577.339 Å (the green line), 6300.304 Å and 6363.776 Å (the two red lines) -in the coma of comets and determine the parent species of the oxygen atoms using the ratio of the green-to-red-doublet emission intensity, I 5577 /(I 6300 + I 6364 ), (hereafter the G/R ratio) and the line velocity widths. Methods. We acquired high-resolution spectroscopic observations at the ESO Very Large Telescope of comets C/2002 T7 (LINEAR), 73P-C/Schwassmann-Wachmann 3, 8P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 30 publications
7
38
1
Order By: Relevance
“…The errors correspond to the standard deviation of the 12 spectra. Considering the theoretical production rates of Raghuram & Bhardwaj (2013; see Table 1 of Decock et al (2015), the 1 S/ 1 D ratio corresponding to the G/R ratio), these results confirm that H 2 O is the main parent molecule that photodissociates to produce oxygen atoms when the comet is observed at a heliocentric distance of r ∼ 1 au. This agrees with previous analyses reported for other comets (Cochran 1984(Cochran , 2008Capria et al 2010;Decock et al 2013, and references therein).…”
Section: [Oi] Linessupporting
confidence: 62%
See 1 more Smart Citation
“…The errors correspond to the standard deviation of the 12 spectra. Considering the theoretical production rates of Raghuram & Bhardwaj (2013; see Table 1 of Decock et al (2015), the 1 S/ 1 D ratio corresponding to the G/R ratio), these results confirm that H 2 O is the main parent molecule that photodissociates to produce oxygen atoms when the comet is observed at a heliocentric distance of r ∼ 1 au. This agrees with previous analyses reported for other comets (Cochran 1984(Cochran , 2008Capria et al 2010;Decock et al 2013, and references therein).…”
Section: [Oi] Linessupporting
confidence: 62%
“…This decontamination was made by substracting a C 2 synthetic spectrum fitted on another C 2 cometary line that appears to be close to the [OI] green line (at 5577.541 Å). More details about the creation of the C 2 synthetic spectrum and its subtraction are given in Rousselot et al (2012) and Decock et al (2015). Figure 1 presents a spectrum of the 5577.339 Å cometary oxygen line region.…”
Section: [Oi] Linesmentioning
confidence: 99%
“…Decock et al (2015) analyzed several ESOʼs VLT observed high-resolution green-and red-doublet emission line spectra on various comets. CO 2 mixing ratios are derived in these comets by comparing the ESO VLT observations with modeled G/R ratio profiles (Decock et al 2015). The model calculated G/R ratio profile is presented on 67P in Figure 11.…”
Section: Derivation Of Co and Co 2 Volume Mixing Ratios Relativementioning
confidence: 99%
“…This model has been applied on several comets and results have been compared with the Earth-based observations (Bhardwaj et al 1996;Bhardwaj 1999;Bhardwaj & Raghuram 2011, 2014Decock et al 2015). The model calculations for comets 103P/Hartley2 and 1P/ Halley have shown that suprathermal electron impact is an important excitation process in the formation of CO(a 3 Π), which is more important than the photodissociation of CO 2 (Bhardwaj & Raghuram 2011;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation